F-spondin regulates neuronal survival through activation of disabled-1 in the chicken ciliary ganglion - Peterziel, Heike; Sackmann, T.; Strelau, Jens; Kuhn, P. H.; Lichtenthaler, S. F.; Marom, K.; Klar, A.; Unsicker, Klaus (Molecular and cellular neuroscience, 2011)
The extracellular membrane-associated protein F-spondin has been implicated in cell-matrix and cell-cell adhesion and plays an important role in axonal pathfinding. We report here that F-spondin is expressed in non-neuronal cells in the embryonic chicken ciliary ganglion (CG) and robustly promotes survival of cultured CG neurons. Using deletion constructs of F-spondin we found that the amino-terminal Reelin/Spondin domain cooperates with thrombospondin type 1 repeat (TSR) 6, a functional TGFβ-activation domain. In ovo treatment with blocking antibodies raised against the Reelin/Spondin domain or the TSR-domains caused increased apoptosis of CG neurons during the phase of programmed cell death and loss of about 30% of the neurons compared to controls. The Reelin/Spondin domain receptor - APP and its downstream signalling molecule disabled-1 are expressed in CG neurons. F-spondin induced rapid phosphorylation of disabled-1. Moreover, both blocking the central APP domain and interference with disabled-1 signalling disrupted the survival promoting effect of F-spondin. Taken together, our data suggest that F-spondin can promote neuron survival by a mechanism involving the Reelin/Spondin and the TSR domains.